How Job Satisfaction and Organizational Commitment Affect the Organizational Citizenship Behavior of Factory Employees: The Role of Psychological Contract as a Mediator - Wibowo, Ardy; Syah, Toufan Aldian; Harahap, Ridho Satria; Fatmasari, Ayu; Nurcholis, Anugrah Wing (DAS Institute, 2024)
During the increasingly heated global competition, employee performance is considered the key to success for the organization. Therefore, management must establish effective strategies and policies to stimulate and encourage increased employee performance. This study analyzes the effect of job statistics and organizational commitment on organizational citizenship behavior (OCB). The sampling method used in this research is probability sampling with a sample of 346 respondents and uses a questionnaire as a data collection method. The data analysis used is the validity and reliability of the instrument, hypothesis testing, and path analysis using the SmartPLS 4.0 program. In this study, the theoretical and managerial implications are discussed further. The results of this study indicate that job satisfaction and organizational commitment do not directly affect organizational citizenship behavior. However, the psychological contract is essential in mediating job satisfaction and organizational loyalty to organizational citizenship behavior